2021
DOI: 10.1093/mnras/stab1470
|View full text |Cite
|
Sign up to set email alerts
|

The mass budget for intermediate-mass black holes in dense star clusters

Abstract: Intermediate-mass black holes (IMBHs) could form via runaway merging of massive stars in a young massive star cluster (YMC). We combine a suite of numerical simulations of YMC formation with a semi-analytic model for dynamical friction and merging of massive stars and evolution of a central quasi-star, to predict how final quasi-star and relic IMBH masses scale with cluster properties (and compare with observations). The simulations argue that inner YMC density profiles at formation are steep (approaching isot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Our prescription for estimating the IMBH mass in our population synthesis results gives a mean IMBH mass of about 5×10 3 M and a median mass of about 1.5 × 10 3 M . These estimated masses are consistent with constraints derived from simulations of young massive clusters and semi-analytical estimates for BH growth in dense environments (Antonini et al 2019;Antonini & Gieles 2020;Shi et al 2021). Using the initial stellar cluster mass distribution from Schaerer & Charbonnel (2011) in our population synthesis approach, we found that most of the stellar clusters that aggregate to form the NSC have initial masses between ∼ 10 5.5 to ∼ 10 6.5 M .…”
Section: Imbh Formation and Growth In Stellar Clusterssupporting
confidence: 84%
“…Our prescription for estimating the IMBH mass in our population synthesis results gives a mean IMBH mass of about 5×10 3 M and a median mass of about 1.5 × 10 3 M . These estimated masses are consistent with constraints derived from simulations of young massive clusters and semi-analytical estimates for BH growth in dense environments (Antonini et al 2019;Antonini & Gieles 2020;Shi et al 2021). Using the initial stellar cluster mass distribution from Schaerer & Charbonnel (2011) in our population synthesis approach, we found that most of the stellar clusters that aggregate to form the NSC have initial masses between ∼ 10 5.5 to ∼ 10 6.5 M .…”
Section: Imbh Formation and Growth In Stellar Clusterssupporting
confidence: 84%
“…Of course, other formation processes for IMBHs have been proposed, including: (i) runaway mergers in globular star clusters (e.g. Portegies Zwart & McMillan 2002 ;G ürkan, Freitag & Rasio 2004 ;Gonz ález et al 2021 ;Shi, Grudi ć & Hopkins 2021 ), (ii) hyper-Eddington accretion on to stellar-mass black holes (e.g. Ryu et al 2016 ), (iii) direct collapse of hypermassive quasi-stars (e.g.…”
mentioning
confidence: 99%
“…Observations have demonstrated the existence of supermassive black holes (BHs) with masses Mbh ∼ 10 9 M in quasars at very high redshift (z 7) when the Universe was less than a billion years old (e.g., Fan et al 2001;Wang et al 2021), which implies that these BHs must accrete rapidly from their "seeds" (Inayoshi et al 2020). The physical origin of these seeds remains deeply uncertain, but popular models including direct collapse of super-massive stars with masses ∼ 10 4 − 10 6 M (e.g., Begelman et al 2006;Regan et al 2017;Corbett Moran et al 2018;Chon & Omukai 2020), runaway mergers in globular clusters (e.g., Portegies Zwart et al 2004;Boco et al 2020;Alister Seguel et al 2020;Kremer et al 2020;Rizzuto et al 2021;Shi et al 2021;Fragione et al 2021), remnants from Population III stars (e.g., Madau & Rees 2001;Ryu et al 2016), and relics of "standard" stellar evolution (e.g. Population II) stars generally produce seeds with masses 10 4 M .…”
Section: Introductionmentioning
confidence: 99%